Quantum Chromodynamics and the Pomeron - Forshaw, J.R; Ross, D.A (Cambridge University Press, 1998)
This volume describes the Pomeron, an object of crucial importance in very high energy particle physics. Starting with a general description of the Pomeron within the framework of Regge theory, the emergence of the Pomeron within scalar field theory is discussed, providing a natural foundation on which to develop the more realistic case of QCD. The reggeization of the gluon is demonstrated and used to build the Pomeron of perturbative QCD. The dynamical nature of the Pomeron and its role in small-x deep inelastic scattering and in diffractive scattering is also examined in detail. The volume concludes with a study of the colour dipole approach to high energy scattering and the explicit role of unitarity corrections. This book will be of interest to theoretical and experimental particle physicists, and applied mathematicians. First published in 1997, this title has been reissued as an Open Access publication.